Educação ambiental e resíduos sólidos: formação de professores do ensino fundamental e médio (Revista de Cultura e Extensão USP, 2009)
Environmental education is one of the most powerful ways of facing the social problems of the contemporary. We know also that there is a great demand from teachers of basic education by interactions with the university for the development of training experience involving environmental issues. These reasons have led a team of ESALQ, Department of Environmental Protection and other institutions of the city of Piracicaba-SP to develop a course on environmental education and solid waste for teachers of schools in the ofﬁ cial teaching network of Piracicaba. The objective of the course was to train educators to develop projects aimed at environmental issues, with emphasis on management of waste. The basic guideline is to encourage and propagate practices and projects in environmental education from the school and teachers. The lessons of the course were taught by professors from the University and guests of the Municipal Secretary of Defense of the Environment of Piracicaba. The course formed twenty-three teachers from the state public education. As a result, there was the preparation of teachers for environmental issues and the motivation to develop new partnerships on this theme, involving the schools of basic education and the University.